Strategies of state penetration: a network analysis of community governance in Shanghai - Tian, Felicia F.; Chen, Lin; Wang, Yihan (Frontiers in Political Science, 2024)
Introduction The Chinese state has been found to penetrate community participation to strengthen state infrastructure power, but understanding of these strategies remains equivocal. Methods This paper collect complete network data from a sample of 112 residents who were active in community activities in Kang community in Shanghai, China. Kang is an award-winning community for its active participation and excellent governance. We examine the strategies of state penetration on the relation between residents' committee (RC) and the thick network through routine community activities. Results The network is indeed horizontal (rather than hierarchical) around the RC. Instead of manifesting state power, popularity within the network translates to decision-making power in deciding routine community activities. However, residents with high network popularity are affiliated with the state, and this association may be generated by the state itself through a deliberate process of cultivation and co-optation. Discussion These findings shed light on the nuanced strategies of state penetration. Rather than overt suppression or infiltration, the state exerts authority over a horizontal network, which ensures that self-organized community participation occurs under state domination.